2020
DOI: 10.1159/000506446
|View full text |Cite
|
Sign up to set email alerts
|

Complete Response of Recurrent Small Cell Carcinoma of the Uterine Cervix to Paclitaxel, Carboplatin, and Bevacizumab Combination Therapy

Abstract: We report a case of recurrent small cell carcinoma of the uterine cervix that showed a complete response to paclitaxel, carboplatin, and bevacizumab (TC + Bev) combination therapy. Small cell carcinoma of the uterine cervix is extremely rare, with an incidence of only 1.3% in Japan, and a poor outcome. The patient was a 62-year-old woman with a chief complaint of irregular vaginal bleeding. Magnetic resonance imaging showed a 10-cm irregular mass from the uterine corpus's posterior wall to the cervix. Abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first was a case of small cell carcinoma, for which TC and bevacizumab therapy without bevacizumab single maintenance therapy was administered, and the status of no recurrence was maintained at 24 months after TC and bevacizumab therapy. 21 The second was a case of small-cell carcinoma, for which a paclitaxel, cisplatin, and bevacizumab regimen without bevacizumab single maintenance therapy was administered; however, the time from discontinuation of the therapy to recurrence was 2 months and the patient was alive at 16 months after recurrence. 22 No adverse events associated with bevacizumab were reported in these two cases; however, the two patients were alive and were not followed up until death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first was a case of small cell carcinoma, for which TC and bevacizumab therapy without bevacizumab single maintenance therapy was administered, and the status of no recurrence was maintained at 24 months after TC and bevacizumab therapy. 21 The second was a case of small-cell carcinoma, for which a paclitaxel, cisplatin, and bevacizumab regimen without bevacizumab single maintenance therapy was administered; however, the time from discontinuation of the therapy to recurrence was 2 months and the patient was alive at 16 months after recurrence. 22 No adverse events associated with bevacizumab were reported in these two cases; however, the two patients were alive and were not followed up until death.…”
Section: Discussionmentioning
confidence: 99%
“…23 These findings indicate that the TC regimen is less effective than the EP or IP regimens, and that the EP or IP regimens should be recommended as the first-line chemotherapy for NEC of the cervix. In the two abovementioned case reports, 21,22 the EP regimen was administered as the first-line treatment, and both cases had a relatively good course. The TC plus Abbreviations: OS, overall survival; PFI, platinum-free interval; PFS, progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that EP is less toxic than VAC. In addition, the EP, TP, or TC regimen has been proven effective in specific clinical situations [50,51]. However, Wang discovered that the combination of etoposide and platinum did not result in an improved overall survival rate after surgery when compared to the combination of platinum and paclitaxel (p = 0.71).…”
Section: Multimodality Therapymentioning
confidence: 99%
“…The patient was treated with 8 cycles of TC + bevacizumab and achieved CR with a progression-free survival (PFS) of more than 24 months. 29 Although the evidence from case reports is weak, their results indicate the potential benefits of anti-angiogenic drugs in SCCC treatment.…”
Section: Introductionmentioning
confidence: 99%